Laboratory tests for identification or exclusion of heparin induced thrombocytopenia: HIT or miss? - Favaloro, Emmanuel J. (American journal of hematology, 2018)
Heparin induced thrombocytopenia (HIT) is a potentially fatal condition that arises subsequent to formation of antibodies against complexes containing heparin, usually platelet‐factor 4‐heparin (“anti‐PF4‐heparin”). Assessment for HIT involves both clinical evaluation and, if indicated, laboratory testing for confirmation or exclusion, typically using an initial immunological assay (“screening”), and only if positive, a secondary functional assay for confirmation. Many different immunological and functional assays have been developed. The most common contemporary immunological assays comprise enzyme‐linked immunosorbent assay [ELISA], chemiluminescence, lateral flow, and particle gel techniques. The most common functional assays measure platelet aggregation or platelet activation events (e.g., serotonin release assay; heparin‐induced platelet activation (HIPA); flow cytometry). All assays have some sensitivity and specificity to HIT antibodies, but differ in terms of relative sensitivity and specificity for pathological HIT, as well as false negative and false positive error rate. This brief article overviews the different available laboratory methods, as well as providing a suggested approach to diagnosis or exclusion of HIT.